1999
DOI: 10.1038/sj.sc.3100874
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of magnesium on lipid peroxidation and axonal function after experimental spinal cord injury

Abstract: Study design: An experimental study examining the neuroprotective eect of magnesium on axonal function and lipid peroxidation in a rat model of acute traumatic spinal cord injury. Objective: To determine the eectiveness of postinjury treatment with magnesium on evoked potentials and lipid peroxidation after spinal cord injury (SCI). Setting: Pamukkale University, Denizli, Turkey. Methods: Spinal cord injury occurred in 30 rats with an aneurysm clip at T9 and the rats were randomly assigned to undergo subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…Magnesium sulfate therapy reduces lipid peroxidation after experimental spinal cord injury (6), long-term hypoxic-ischemic brain damage in 7-d-old rat (7), and the volume of traumatic brain lesions (8). It also facilitates recovery of function following electrolytic cortical injury (9).…”
mentioning
confidence: 99%
“…Magnesium sulfate therapy reduces lipid peroxidation after experimental spinal cord injury (6), long-term hypoxic-ischemic brain damage in 7-d-old rat (7), and the volume of traumatic brain lesions (8). It also facilitates recovery of function following electrolytic cortical injury (9).…”
mentioning
confidence: 99%
“…The concept of dual mechanism in the spinal cord injury was introduced at the beginning of 1900s by Allen who demonstrated that progressive damage occurrs in patients with spinal cord injuries (21). Following SCI, a series of pathological changes occurs in the spinal cord, including bleeding, edema, demyelinization, axonal and neuronal necrosis, and cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Suzer et al [29] have shown with somatosensoryevoked potentials that magnesium has dose-dependent neuroprotective properties and attenuates lipid peroxidation in an acute traumatic spinal cord injury model. In the traumatic spinal cord injury model in rats, Demediuk et al [30] and Lemke et al [31] have reported that following trauma, the tissue level of magnesium falls to a critical value, reaches its initial level in 7 days, and that this fall in the level of magnesium is proportional to the severity of trauma.…”
Section: Discussionmentioning
confidence: 99%